2024
DOI: 10.3390/ani14060840
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nutritional Factors on Fat Content, Fatty Acid Composition, and Sensorial Properties of Meat and Milk from Domesticated Ruminants: An Overview

Eric Ponnampalam,
Hasitha Priyashantha,
Janak Vidanarachchi
et al.

Abstract: The meat and milk products from domesticated ruminants are important foods within a balanced diet, offering a rich source of energy, protein, fats, minerals, and vitamins. The sensorial properties of meat and milk are mainly linked to their fat content and fatty acid composition, which are influenced by the feeding background or nutrient composition of diets. While several studies have investigated the nutritional effects on the fat content and fatty acid profile of ruminant meat and milk, as well as their rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 252 publications
0
3
0
Order By: Relevance
“…Many studies have reported that feed diets supplemented with Schizochytrium spp. biomass led to enhanced nutritional quality in lamb muscle, characterized by a more favorable fatty acid profile and increased DHA and EPA levels (Carvalho et al 2018 ; Díaz et al 2017 ; Fan et al 2019 ; Hopkins et al 2014 ; Meale et al 2014 ; Ponnampalam et al 2016 ; Urrutia et al 2016 ; Xu et al 2021 ). In terms of other algal species, the inclusion of a dinoflagellate (Dinophyceae) in the diet of lambs also led to an increase in EPA and DHA levels in meats (Cooper et al 2004 ; Elmore et al 2005 ), and dietary supplementation with 4% Isochrysis sp.…”
Section: Influence Of Dietary Microalgae Supplementation On Ruminant ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported that feed diets supplemented with Schizochytrium spp. biomass led to enhanced nutritional quality in lamb muscle, characterized by a more favorable fatty acid profile and increased DHA and EPA levels (Carvalho et al 2018 ; Díaz et al 2017 ; Fan et al 2019 ; Hopkins et al 2014 ; Meale et al 2014 ; Ponnampalam et al 2016 ; Urrutia et al 2016 ; Xu et al 2021 ). In terms of other algal species, the inclusion of a dinoflagellate (Dinophyceae) in the diet of lambs also led to an increase in EPA and DHA levels in meats (Cooper et al 2004 ; Elmore et al 2005 ), and dietary supplementation with 4% Isochrysis sp.…”
Section: Influence Of Dietary Microalgae Supplementation On Ruminant ...mentioning
confidence: 99%
“… 3% on a dry matter basis / lamb / day Increased EPA and DHA content (Fan et al 2019 ) Cross ewe lambs Schizochytrium sp . 1.8% on a dry matter basis / lamb / day Increased EPA and DHA content in muscle (Ponnampalam et al 2016 ) Did not affect retail display color of fresh meat Increased lipid oxidation Weaned male Manchego lambs Schizochytrium sp . 2% on a dry matter basis / lamb / day Increased DHA and total n-3 fatty acids content (Díaz et al 2017 ) Wether lambs Schizochytrium sp .…”
Section: Influence Of Dietary Microalgae Supplementation On Ruminant ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Trans fatty acids are not essential and do not attribute any known benefit to human health [99]; on the contrary, they favor the increase in LDL cholesterol levels and originate in the processing of many foods [49,69,100]. Trans fatty acids have been shown to increase the risk of cardiovascular disease more than any other macronutrient [19,101] and substantially increase risk, even with low levels of consumption (1 to 3% of total energy intake), so the World Health Organization recommended in 2003 that trans-fat consumption should be limited to less than 1% of total energy intake [32,59,102].…”
Section: Cholesterolmentioning
confidence: 99%
“…Aquatic buffaloes have high aptitude as a producer of protein of high biological value, so they can reach weights above 500 kg at 3.5 years of age in natural fields in the northern region of Brazil [ 32 ]. There is excellent sensory conformity of the meat of young aquatic buffaloes, compared to the “lean” beef of the zebu, in terms of juiciness and tenderness.…”
Section: Contextualizationmentioning
confidence: 99%